Determination of cut-off and correlates of delay in treatment-seeking of febrile illness: a retrospective analysis - Himanshu K. Chaturvedi; Ram C. Bajpai; Preeti Tiwari (BMC, 2020)
Abstract Background Early diagnosis and treatment of malaria symptoms reduces the risk of severe complication and malaria transmission. However, delay in malaria diagnosis and treatment is a major public health problem in India. The primary aim of the study was to determine cut-off for the delay in seeking treatment of fever, and the secondary aim was to identify the factors associated with delay in malaria-endemic areas of Assam, Northeast India. Methods The present study analysed data from two prior cross-sectional surveys (community- and hospital-based) that was conducted to study the health-seeking behaviour of people residing in high malaria-endemic areas of Assam, Northeast India. The hospital-based survey data were used to determine optimal cut-off for the delay in reporting, and further, used to identify the factors associated with delay using community-based data. Results Mean age of fever cases was similar in both community- and hospital-based surveys (23.1 years vs 24.2 years, p = 0.229). Delay in reporting fever was significantly higher among hospital inpatients compared to community-based fever cases (3.6 ± 2.1 vs 4.0 ± 2.6 days; p = 0.006). Delay of > 2 days showed higher predictive ability (sensitivity: 96.4%, and ROC area: 67.5%) compared to other cut-off values (> 3, > 4, and > 5 days). Multivariable logistic regression analysis revealed that the adjusted odds ratio (aOR) of delay was significantly higher for people living in rural areas (1.52, 95%CI: 1.11-2.09), distance (> 5 km) to health facility (1.93, 95%CI: 1.44-2.61), engaged in agriculture work (2.58, 95%CI: 1.97-3.37), and interaction effect of adult male aged 20-40 years (1.71, 95%CI: 1.06-2.75). Conclusion The delay (> 2 days) in seeking treatment was likely to be twice among those who live in rural areas and travel > 5 km to assess health care facility. The findings of the study are useful in designing effective intervention programmes for early treatment of febrile illness to control malaria.